A Pinus strobus transcription factor PsbHLH1 activates the production of pinosylvin stilbenoids in transgenic Pinus koraiensis calli and tobacco leaves - Kim, Yi Rae; Han, Jung Yeon; Choi, Yong Eui (Frontiers in Plant Science, 2024)
Transcription factors (TFs) play an important role in regulating the biosynthesis of secondary metabolites. In Pinus strobus, the level of methylated derivatives of pinosylvin is significantly increased upon pine wood nematode (PWN) infection, and these compounds are highly toxic to PWNs. In a previous study, we found that the expression of a basic helix-loop-helix TF gene, PsbHLH1, strongly increased in P. strobus plants after infection with PWNs. In this study, we elucidated the regulatory role of the PsbHLH1 gene in the production of methylated derivatives of pinosylvin such as pinosylvin monomethyl ether (PME) and dihydropinoylvin monomethyl ether (DPME). When PsbHLH1 was overexpressed in Pinus koraiensis calli, the production of PME and DPME was significantly increased. Overexpression of the stilbene synthase (PsSTS) and pinosylvin methyl transferase (PsPMT) genes, known as key enzymes for the biosynthesis of methylated pinosylvins, did not change PME or DPME production. Moreover, PME and DPME were not produced in tobacco leaves when the PsSTS and PsPMT genes were transiently coexpressed. However, the transient expression of three genes, PsSTS, PsPMT, and PsbHLH1, resulted in the production of PME and DPME in tobacco leaves. These results prove that PsbHLH1 is an important TF for the pinosylvin stilbene biosynthesis in pine plants and plays a regulatory role in the engineered production of PME and DPME in tobacco plants.